The effect of individual learning on collective foraging in honey bees in differently structured landscapes. (September 2021) - Lemanski, Natalie J.; Cook, Chelsea N.; Ozturk, Cahit; Smith, Brian H.; Pinter-Wollman, Noa
Abstract : The trade-off between exploiting known resources and exploring for new ones is a complex decision-making challenge, particularly when resource patches are variable in quality and heterogeneously distributed in the landscape. Social insect colonies navigate this challenge, in the absence of centralized control, by allocating different individuals to exploration or exploitation based on variation in individual behaviour. To investigate how heritable differences in individual learning affect a colony's collective ability to locate and choose among different quality food resources, we develop an agent-based model and test its predictions empirically using two genetic lines of honey bees ( Apis mellifera ), selected for differences in their learning behaviour. We show that colonies containing individuals that are better at learning to ignore unrewarding stimuli are worse at collectively choosing the highest-quality resource. This work highlights how differences in individual behaviour may have unexpected consequences for the emergence of collective behaviour. Highlights: We examined how individual behaviour affects collective foraging in honey bees. Colonies with more exploiters were better at choosing the best quality food. Optimal proportion of explorers was higher when resources were spatially clumped. Less exploratory workers were best at choosing the highest-quality food patches. Explorers facilitate quick collective decisions and exploiters facilitate accuracy.